2014
DOI: 10.1053/j.gastro.2013.11.049
|View full text |Cite
|
Sign up to set email alerts
|

Increased De Novo Lipogenesis Is a Distinct Characteristic of Individuals With Nonalcoholic Fatty Liver Disease

Abstract: BACKGROUND & AIMS: There have been few studies on the role of de novo lipogenesis in the development of nonalcoholic fatty liver disease (NAFLD). We used isotope analyses to compare de novo lipogenesis and fatty acid flux between individuals with NAFLD and those without, matched for metabolic factors (controls). METHODS: We studied subjects with metabolic syndrome and/or levels of alanine aminotransferase and aspartate aminotransferase >30 mU/L, using magnetic resonance spectroscopy to identify those with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
722
6
9

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 811 publications
(832 citation statements)
references
References 58 publications
(117 reference statements)
28
722
6
9
Order By: Relevance
“…Without altering ChREBP nuclear localization, a diet rich in fructose increases ChREBP binding to DNA nearly 4 fold (Koo et al 2009). Interestingly, dietary fructose more robustly induces DNL in patients with fatty liver disease (Lambert et al 2014). Thus, dietary fructose contributes to the development of NAFLD through increased DNL and NAFLD feeds forward to increase DNL from fructose.…”
Section: De Novo Lipogenesismentioning
confidence: 99%
“…Without altering ChREBP nuclear localization, a diet rich in fructose increases ChREBP binding to DNA nearly 4 fold (Koo et al 2009). Interestingly, dietary fructose more robustly induces DNL in patients with fatty liver disease (Lambert et al 2014). Thus, dietary fructose contributes to the development of NAFLD through increased DNL and NAFLD feeds forward to increase DNL from fructose.…”
Section: De Novo Lipogenesismentioning
confidence: 99%
“…VLDL secretion represents the efflux pathway of fat from the liver and, therefore, a reduction in this pathway can partially explain the increase in liver fat found in carriers of the PNPLA3 mutation [86]. Intrahepatic de novo lipogenesis is believed to be a driver of the increase in hepatic fat content [87]. Recently, a study showed that carriers of the rs738409[G] allele have lower de novo lipogenesis as compared to non-carriers due to a reduction in liver SREBP1c mRNA levels [88].…”
Section: Reviewmentioning
confidence: 99%
“…T2D is also associated with raised plasma TAG levels and a greater fractional contribution of hepatic de novo lipogenesis (DNL), representing the synthesis of fatty acids from acetyl units (18) , to TAG secretion (19) . In NAFLD, glycerolipid accumulates in hepatocytes because of an imbalance between fatty acid uptake (from NEFA and dietary lipids) plus synthesis (via DNL) relative to fatty acid disposal by mitochondrial β-oxidation plus secretion as TAG in VLDL (20)(21)(22) . In the healthy fasted state, the major sources of substrate for hepatic TAG secretion are NEFA derived from adipose lipolysis with a smaller contribution of NEFA from dietary chylomicrons that escape uptake by extra hepatic tissues and a negligible contribution of DNL (18) .…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
“…In the healthy fasted state, the major sources of substrate for hepatic TAG secretion are NEFA derived from adipose lipolysis with a smaller contribution of NEFA from dietary chylomicrons that escape uptake by extra hepatic tissues and a negligible contribution of DNL (18) . NAFLD is associated with increased fatty acid supply by adipose tissue lipolysis (22) and an increased fractional contribution of DNL to TAG secretion (20)(21)(22) from <5 % in controls to 15-20 % in patients (20,22) . Both the rate of VLDL-TAG secretion derived from DNL and the fractional contribution of DNL to VLDL secretion are elevated in NAFLD and correlate with liver fat content (22) .…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%